Edge AI for condition monitoring - Hu, Zinan (Nanyang Technological University, 2024)
Condition monitoring plays a critical role in safeguarding the operational integrity and efficiency of edge devices such as batteries, automobiles, and mobile phones. Presently, prevailing solutions for condition monitoring heavily rely on Artificial Intelligence (AI), with AI models trained and deployed in cloud-based or centralized computing systems. To solve the problems, this work emphasizes the Edge AI paradigm in contrast, where in AI models are executed on edge devices in close proximity to the batteries or automobiles. This approach facilitates expedited remedial actions and reduces the cost associated with data transmission.